Pengaruh Media Pembelajaran Teachmint dan Keaktifan Belajar Terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Ekonomi di SMA Negeri 4 Sumatera Barat - Nur Aini; Jimi Ronald; Vivina Eprillison (SAKOLA: Journal of Sains Cooperative Learning and Law, 2024)
This research aims to analyze the influence of Teachmint learning media and active learning on the learning outcomes of class X students in economics subjects at SMA Negeri 4 West Sumatra. The type of research used was quantitative with a sample of 71 students consisting of 35 experimental class students and 36 control class students. The research instrument used tests of validity, reliability, level of difficulty, discrimination, normality, homogeneity, and two-way ANOVA with the help of SPSS 18.0. The results of the research show: (1) The economic learning outcomes of students taught using Teachmint media are higher than conventional media, (2) The learning outcomes of students with high activity who are taught by Teachmint are higher than conventional, (3) The learning outcomes of students with low activity who are taught Teachmint is higher than conventional, (4) There is an interaction between learning media and active learning on students' economic learning outcomes.